2008
DOI: 10.1534/genetics.108.098244
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cells, Their Niches and the Systemic Environment: An Aging Network

Abstract: Stem cells have a fascinating biology and offer great prospects for therapeutic applications, stimulating intense research on what controls their properties and behavior. Although there have been significant advances in our understanding of how local microenvironments, or niches, control the maintenance and activity of stem cells, it is much less well understood how stem cells sense and respond to variable external, physiological, or tissue environments. This review focuses on the multidirectional interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
86
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(87 citation statements)
references
References 92 publications
1
86
0
Order By: Relevance
“…Joshi et al suggested that mammalian target of rapamycin signaling plays an important role in muscle atrophy after massive RCTs in a rat model and mediates rotator cuff fatty infiltration via SREBP‐1 and PPARγ 23. However, it is doubtful that the population of multipotent stem cells is sufficient in the old individual; stem cell numbers and activities decrease during aging 42. As another mechanism of fatty infiltration, a previous study suggested that fatty infiltration after tendon release was associated with substantial, irreversible architectural changes in the muscle, such as an increase in the pennation angle and shortening of the muscle fibers 43.…”
Section: Discussionmentioning
confidence: 99%
“…Joshi et al suggested that mammalian target of rapamycin signaling plays an important role in muscle atrophy after massive RCTs in a rat model and mediates rotator cuff fatty infiltration via SREBP‐1 and PPARγ 23. However, it is doubtful that the population of multipotent stem cells is sufficient in the old individual; stem cell numbers and activities decrease during aging 42. As another mechanism of fatty infiltration, a previous study suggested that fatty infiltration after tendon release was associated with substantial, irreversible architectural changes in the muscle, such as an increase in the pennation angle and shortening of the muscle fibers 43.…”
Section: Discussionmentioning
confidence: 99%
“…Stem cell function is essential for renewing cellular content of the organism during aging and tissue repair (4)(5)(6). The frequency of divisions in adult stem cell populations depends on tissue-specific requirements for cell production and can be modulated in response to environmental and behavioral stimuli (7).…”
Section: Discussionmentioning
confidence: 99%
“…Cell renewal is essential for maintaining tissue function over the lifetime of the organism (4). To replace damaged and aging cellular content, comparatively small populations of adult stem cells reside within specialized microenvironments called stem cell niches, where they undergo repeated mitotic divisions, generating new stem and differentiated cells (5).…”
mentioning
confidence: 99%
“…Comprehensive reviews of the Drosophila testis include those by Fuller (Fuller, 1993) and Davies and Fuller (Davies and Fuller, 2008). Recent reviews that focus on specific topics relevant to Drosophila testis stem cells include those on adhesion (Marthiens et al, 2010), asymmetric division , aging and systemic regulation (Drummond-Barbosa, 2008;Jasper and Jones, 2010). For a comprehensive review of the Drosophila ovary stem cell niche, see Xie et al (Xie et al, 2008); a recent review by Fuller and Spradling (Fuller and Spradling, 2007) compares and contrasts the testis and ovary stem cell niches.…”
Section: Introductionmentioning
confidence: 99%